Rekonstruksi Batasan Hak Privasi dalam Penyidikan Tindak Pidana Narkotika Berbasis Transaksi Elektronik - Salman Alfarisi; Kartina Eka Ningsih; Firdaus (LP3M Universitas Al-Qolam Malang, 2026)
This research examines the urgency and offers a conceptual reconstruction of the regulatory protection of suspects' privacy rights in the investigation of electronic transaction-based narcotics crimes. Currently, there is a conflict of norm between the extensive interception authority of investigators under Law Number 35 of 2009 concerning Narcotics and the privacy rights guaranteed by Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). Through a normative legal research method utilizing statute and conceptual approaches, this study finds that current positive law, including the new Criminal Procedure Code (Law Number 20 of 2025), has not rigidly regulated the depth limits of digital data extraction. This legal vacuum legitimizes random fault-finding practices that potentially violate the principle of due process of law. Therefore, based on the Theory of Dignified Justice, this research recommends the need for a reconstruction of digital criminal procedural law. This reconstruction is realized through the integration of the data minimization principle, the implementation of specific court-issued digital extraction permit mechanisms, and the obligation to maintain system audit trails at every stage of the investigation. This aims to ensure a proportional balance between the effectiveness of combating narcotics crimes and the protection of human rights.